Nuclear Power and Sustainable Energy Policy : Promises and Perils - Kessides, Ioannis N. (World Bank, 2012)
The author examines the challenges and opportunities of nuclear power in meeting the projected large absolute increase in energy demand, especially electricity, throughout the industrialized and developing world, while helping to mitigate the threat of climate change. A significant global nuclear power deployment would engender serious risks related to proliferation, safety, and waste disposal. Unlike renewable sources of energy, nuclear power is an unforgiving technology because human lapses and errors can have ecological and social impacts that are catastrophic and irreversible. However, according to some analysts, advances in the design of nuclear reactors may have reduced their associated risks and improved their performance. Moreover, while a variety of renewable energy sources (hydro, wind, modern biomass, solar) will play important roles in the transition to a low-carbon economy, some analysts perceive that nuclear power is the only proven technology for generating electricity that is both largely carbon-free, not location specific (as with wind, hydro and solar), and amenable to significant scaling up. Thus given the projections of threats from climate change, and if the considerable strain experienced by world energy markets in recent years is a harbinger of things to come, then there is a rationale for examining the pros and cons of nuclear power as a supply option within low-carbon strategies. It should be noted that despite the emerging centrality of climate change and security of supply in the energy policy debate, nuclear power is still viewed with a great deal of skepticism and in fact continues to elicit considerable opposition. Indeed the views on nuclear power in the context of sustainable energy policy are highly divergent. A thorough evaluation of all aspects of the issue is warranted.